WAR, POLITICS AND IDEOLOGY IN THE 21ST CENTURY (Годишен зборник на Филозофски факултет - Скопје, 2025)
War is one of the most studied phenomena at the beginning of the 21st century. Due to its constant transformation and the different ways of its manifestation, the need for its observation is also growing. There is a wide range of interpretations of war because it affects all areas of social life, politics, economics, diplomacy and religion. Theprevailing uncertainty and fear of future wars and conflicts were seen as a reason for strengthening military capacities and increasing defense spending of states and international organizations, which contributed to a new arms race and strengthening the militaristic mentality and influence of military force as a driver in foreign policy.We pay particular attention to the causes of wars and the policies that encourage war to the extreme, both in terms of the engagement of forces and resources, and in terms of the manifestation of violence. Historical experience shows that governments and their leaders are guided by national interests and ideologies, and are not at all hesitant about starting a war, viewing military force as a means to achieve political goals, while not paying attention to the repercussions on international law and the preservation of peace in the world.